RP-HPLC Estimation of Azelnidipine and Chlorthalidone in Bulk and Combined Dosage Forms - Singh, Anamika; Narsinghani, Tamanna (Indian Journal of Pharmaceutical Education and Research)
Objectives: A simple, sensitive, robust, precise and efficient RP-HPLC approach for the simultaneous determination of Azelnidipine and Chlorthalidone in combination. Materials and Methods: As per ICH Q2 (R1) guidelines, the final chromatographic conditions were optimized with a mobile phase ratio of (30:70% v/v) in Water containing 0.1% formic acid: Methanol containing 0.1% formic acid at a flow rate of 1 mL/min, column temperature of 35ºC, injection volume of 20 μL, Interstil C18 analytical column. Results: Azelnidipine and Chlorthalidone reported retention times of 2.32 min and 4.09 min, respectively. Validation of method was found to be linear in the range of 0.4-1.2 μg/mL for Azelnidipine and 0.63-1.88 μg/mL for Chlorthalidone. The % Recovery was found to be 99.96-100.18% and 99.91-100.71 for Azelnidipine and Chlorthalidone respectively. The Precision results for both drugs were within the limits while expressed Intraday and Interday. For Azelnidipine, the LOD and LOQ were reported to be 0.164 μg/mL and 0.498 μg/mL, respectively and for Chlorthalidone, 0.148 μg/mL and 0.448 μg/mL. As per ICH Q1A (R2) guidelines, the combination was subjected to acid, base, oxidation, thermal and photolysis stress conditions. Conclusion: The results suggest that the developed method could be used for the routine analysis of the drug sample in bulk and combined dosage forms for the determination of shelf life and storage conditions of the formulations.
Keywords: RP-HPLC; Azelnidipine; Chlorthalidone; Forced Degradation Studies; ICH Guidelines.